Cyclic vomiting syndrome: Pathophysiology, comorbidities, and future research directions. (26th June 2019) - Hasler, William L.; Levinthal, David J.; Tarbell, Sally E.; Adams, Kathleen A.; Li, B U. K.; Issenman, Robert M.; Sarosiek, Irene; Jaradeh, Safwan S.; Sharaf, Ravi N.; Sultan, Shahnaz; Venkatesan, Thangam
Abstract: Cyclic vomiting syndrome (CVS) is characterized by severe episodic emesis in adults and children. Cannabinoid hyperemesis syndrome is an increasingly recognized CVS‐like illness that has been associated with chronic cannabis use. There are significant gaps in our understanding of the pathophysiology, clinical features, comorbidities, and effective management options of CVS. Recommendations for treating CVS are based on limited clinical data, as no placebo‐controlled, randomized trials have yet been conducted. Diseases associated with CVS, including migraine, mitochondrial disorders, autonomic dysfunction, and psychiatric comorbidities, provide clues about pathophysiologic mechanisms and suggest potential therapies. We review our current understanding of CVS and propose future research directions with the aim of developing effective therapy. Establishing a multicenter, standardized registry of CVS patients could drive research on multiple fronts including developing CVS‐specific outcome measures to broaden our understanding of clinical profiles, to serve as treatment end points in clinical trials, and to provide a platform for patient recruitment for randomized clinical trials. Such a robust database would also facilitate conduct of research that aims to determine the underlying pathophysiological mechanisms and genetic basis for CVS, as well as identifying potential biomarkers for the disorder. Soliciting government and industry support is crucial to establishing the necessary infrastructure and achieving these goals. Patient advocacy groups such as the Cyclic Vomiting Syndrome Association (CVSA), which partner with clinicians and researchers to disseminate new information, to promote ongoing interactions between patients, their families, clinicians, investigators, to support ongoing CVS research and education, must be an integral part of this endeavor.